ANALISIS PENDAPATAN DAN KELAYAKAN USAHA KERIPIK UBIKAYU PADA INDUSTRI PUNDI MASDI KOTA PALU - Basra Pasau,Made Antara, Lien Damayanti, Mariam A. (AGROTEKBIS, 2015)
This study aims to determine amount of income and the feasibility of potato chips on Pundi Mas Industry. The research was conducted in Palu City in December 2014. Determination of the respondents in this research is using purposive method, the selected respondents are leaders and employees of Pundi Mas. The data used in this study is sourced from the primary data and secondary data. the analysis tool used in this research is Revenue Analysis and Feasibility Analysis. Results showed that income earned in the month of December 2014 is Rp. 22.259.250,34 or Rp. 267.111.004 and potato chips is viable businesses with R/C value of 1,77.